2022
DOI: 10.5194/egusphere-2022-627
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Novel Arctic sea ice data assimilation combining ensemble Kalman filter with a Lagrangian sea ice model

Abstract: Abstract. Advanced data assimilation (DA) methods, widely used in geophysical and climate studies to merge observations with numerical models, can improve the state estimates and consequent forecasts. We interface the deterministic Ensemble Kalman filter (DEnKF) to the Lagrangian sea ice model, neXtSIM. The ensemble is generated by perturbing the atmospheric and oceanic forcing throughout the simulations and randomly initialized ice cohesion. Our ensemble-DA system assimilates sea ice concentration (SIC) from … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 43 publications
(62 reference statements)
0
2
0
Order By: Relevance
“…The MITgcm model has been paired with a local error subspace transform Kalman filter (Mu et al ., 2018). Other examples, such as the TOPAZ4 (Sakov et al ., 2012; Xie et al ., 2018), the NEMO‐LIM2 (Massonnet et al ., 2013), and the neXtSIM model (Cheng et al ., 2023; Richter et al ., 2023; Sampson et al ., 2021), all use different flavours of the ensemble Kalman filter (EnKF) (Evensen et al ., 2022). It is planned that DA capabilities will also be added to neXtSIM DG$$ {}_{\mathrm{DG}} $$.…”
Section: Introductionmentioning
confidence: 99%
“…The MITgcm model has been paired with a local error subspace transform Kalman filter (Mu et al ., 2018). Other examples, such as the TOPAZ4 (Sakov et al ., 2012; Xie et al ., 2018), the NEMO‐LIM2 (Massonnet et al ., 2013), and the neXtSIM model (Cheng et al ., 2023; Richter et al ., 2023; Sampson et al ., 2021), all use different flavours of the ensemble Kalman filter (EnKF) (Evensen et al ., 2022). It is planned that DA capabilities will also be added to neXtSIM DG$$ {}_{\mathrm{DG}} $$.…”
Section: Introductionmentioning
confidence: 99%
“…The main correction comes from the use of CryoSat-2 data; the assimilation of SMOS reduced the error in the thin ice about 11 % and 22 % in March and in November respectively, without degradation in the other variables. Yang et al (2014) and Mu et al (2018b) tested the localized singular evolutive interpolated Kalman filter to integrate thickness data and showed an overall error that is similar to the Pan-Arctic Ice Ocean Modeling and Assimilation System (PIOMAS) (Zhang and Rothrock, 2003) when compared to independent in situ measurements.Finally, Cheng et al (2023) recently showed, in the standalone Lagrangian sea-ice model neXtSIM interfaced to a deterministic ensemble Kalman filter (EnKF) scheme in a multivariate manner, that improvements in SIT estimates indicate the importance of assimilating weekly CS2SMOS SIT, while the improvements of sea-ice concentration (SIC) and ice extent are moderate but benefit from daily correction from OSI-SAF SIC. In this study, we extend an operational 3DVar data assimilation (DA) scheme, OceanVar, employed in the production of global and regional ocean reanalysis and forecasts (Storto et al, 2019a;Escudier et al, 2021;Lima et al, 2021;Ciliberti et al, 2022), to treat sea-ice concentration (SIC) and thickness (SIT) data.…”
Section: Introductionmentioning
confidence: 99%